Offensive Language and Serious Harm: Application of the Films, Videos, and Publications Classification Act 1993 - Wilson, Kate (Victoria University of Wellington Law Review, 2017)
Section 3A of the Films, Videos, and Publications Classification Act 1993 allows age-restriction of a publication if it contains highly offensive language that is likely to cause serious harm. The Office of Film and Literature Classification and the Film and Literature Board of Review have failed to apply this section consistently. They have categorised the same word as both offensive and not offensive and the same harm as serious and not serious throughout their reports. They have also avoided substantive consideration of the New Zealand Bill of Rights Act 1990. An analysis of social science research provides a solid grounding on which the requirements of the section could be applied. Additionally, a more thorough analysis of the severity of harm could be reached through a comprehensive application of the New Zealand Bill of Rights Act 1990. Harm should be balanced against the merits of the publication and the importance of freedom of expression in order to determine whether it is serious enough to justify a restriction. This approach would lead to fewer restrictions under s 3A and consistency throughout future decisions.